SPICE-Based Multiphysics Model to Analyze the Dynamics of Ferroelectric Negative-Capacitance-Electrostatic MEMS Hybrid Actuators - Raman, Raghuram Tattamangalam; Ajoy, Arvind (IEEE transactions on electron devices, 2020)
We propose a Simulation Program with Integrated Circuit Emphasis (SPICE)-based multiphysics framework to model ferroelectric negative-capacitance-electrostatic microelectromechanical systems (MEMS) hybrid actuators. Our approach couples the nonlinear dynamics of both the ferroelectric capacitor and the MEMS actuator. Using this framework, we examine the dynamic response and the energy consumed during pull-in switching of the hybrid actuator. We predict a significant reduction in the dynamic pull-in and pull-out voltages and the energy consumed by the hybrid actuator compared with the standalone MEMS actuator. We also predict that the pull-in time of the hybrid actuator is, however, larger than that of the standalone actuator. Nevertheless, we show that one can tradeoff a small part of the reduction in actuation voltage to achieve identical pull-in times in the hybrid and standalone MEMS actuators while still consuming substantially lower energy in the former compared with the latter. Our analysis approach is compatible with standard circuit simulators and is, hence, suitable for analysis and evaluation of various heterogeneous systems consisting of hybrid MEMS actuators and other electronic devices.